Analisis Penentuan Komoditas Unggulan Tanaman Pangan Di Kabupaten Sambas - Dewi Kurniati (JURNAL MANAJEMEN MOTIVASI, 2014)
This study aimed to analyze the superior commodity areas of food crops sector in Sambas district and determine commodity of food crops become superior commodities to be developed in Sambas district. The study area is in Sambas district. Data used in this research is secondary data published by BPS Sambas district includes data each subdistrict for food crops sector in 2009 - 2013. The determination of superior commodity used analysis  location quotient (LQ) . The results of the analysis concluded that each food crops have base areas in all sub districts are scattered in Sambas district. These results into suggestions for the Regional Government Sambas district in an effort to increase the PDRB in order to prioritize the development of food crops with superior not ignore other food crops in the planning and implementation of the development.